Heart failure after the Norwood procedure: An analysis of the Single Ventricle Reconstruction Trial - Mahle, William T.; Hu, Chenwei; Trachtenberg, Felicia; Menteer, JonDavid; Kindel, Steven J.; Dipchand, Anne I.; Richmond, Marc E.; Daly, Kevin P.; Henderson, Heather T.; Lin, Kimberly Y.; McCulloch, Michael; Lal, Ashwin K.; et al. (The Journal of heart and lung transplantation, 2018)
Heart failure results in significant morbidity and mortality in young children with hypoplastic left heart syndrome (HLHS) after the Norwood procedure. We studied subjects enrolled in the prospective Single Ventricle Reconstruction (SVR) Trial who survived to hospital discharge after a Norwood operation and were followed up to age 6 years. The primary outcome was heart failure, defined as heart transplant listing after Norwood hospitalization, death attributable to heart failure, or symptomatic heart failure (New York Heart Association [NYHA] Class IV). Multivariate modeling was undertaken using Cox regression methodology to determine variables associated with heart failure. Of the 461 subjects discharged home following a Norwood procedure, 66 (14.3%) met the criteria for heart failure. Among these, 15 died from heart failure, 39 were listed for transplant (22 had a transplant, 12 died after listing, and 5 were alive and not yet transplanted), and 12 had NYHA Class IV heart failure but were never listed. The median age at heart failure identification was 1.28 (interquartile range 0.30 to 4.69) years. Factors associated with early heart failure included post-Norwood lower fractional area change, need for extracorporeal membrane oxygenation, non-Hispanic ethnicity, Norwood perfusion type, and total support time (p < 0.05). By 6 years of age, heart failure developed in nearly 15% of children after the Norwood procedure. Although transplant listing was common, many patients died from heart failure before receiving a transplant or without being listed. Shunt type did not impact the risk of developing heart failure.